Effect of acetylation technique on mechanical behavior and durability of palm fibre vinyl-ester composites. (2020) - Senthilraja, R.; Sarala, R.; Antony, A. Godwin; Seshadhri
Abstract: In natural fiber reinforced polymer (NFRP) composites, there is a lack of good inter-facial adhesion between the hydrophilic cellulose fibers due to their inherent incompatibility. High water and moisture absorption of the cellulose fibres causes swelling, dimensional instability, poor mechanical properties. This work focuses on eliminating the swelling effect of the palm fiber composite by Acetylation. This acetylated palm fiber composites reduce manufacturing cost of automobile interiors, door panels, etc. The chemical treatment improved the tensile strength till 6% concentration. The ANOVA study was carried out to reveal the effects of concentration and soaking period on strength of fiber composites.